The effect of vitamin D supplementation on knee osteoarthritis, the VIDEO study: a randomised controlled trial. Issue 11 (November 2016) - Arden, N.K.; Cro, S.; Sheard, S.; Doré, C.J.; Bara, A.; Tebbs, S.A.; Hunter, D.J.; James, S.; Cooper, C.; O'Neill, T.W.; Macgregor, A.; Birrell, F.; et al.
Summary: Objective: Epidemiological data suggest low serum 25-hydroxyvitamin D3 (25-OH-D3 ) levels are associated with radiological progression of knee osteoarthritis (OA). This study aimed to assess whether vitamin D supplementation can slow the rate of progression. Method: A 3-year, double-blind, randomised, placebo-controlled trial of 474 patients aged over 50 with radiographically evident knee OA comparing 800 IU cholecalciferol daily with placebo. Primary outcome was difference in rate of medial joint space narrowing (JSN). Secondary outcomes included lateral JSN, Kellgren & Lawrence grade, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain, function, stiffness and the Get up and Go test. Results: Vitamin D supplementation increased 25-OH-D3 from an average of 20.7 (standard deviation (SD) 8.9) μg/L to 30.4 (SD 7.7) μg/L, compared to 20.7 (SD 8.1) μg/L and 20.3 (SD 8.1) μg/L in the placebo group. There was no significant difference in the rate of JSN over 3 years in the medial compartment of the index knee between the treatment group (average −0.01 mm/year) and placebo group (−0.08 mm/year), average difference 0.08 mm/year (95% confidence interval (CI) [−0.14–0.29], P  = 0.49). No significant interaction was found between baseline vitamin D levels and treatment effect. There were no significant differences for any of the secondary outcome measures. Conclusion: Vitamin D supplementation did not slow the rate of JSN or lead to reduced pain, stiffness or functional loss over a 3-year period. On the basis of these findings we consider that vitamin D supplementation has no role in the management of knee OA.